Communicating uncertainty in cancer prognosis: A review of web-based prognostic tools. Issue 5 (May 2019) - Harrison, Mark; Han, Paul K.J.; Rabin, Borsika; Bell, Madelaine; Kay, Hannah; Spooner, Luke; Peacock, Stuart; Bansback, Nick
Highlights: There are an increasing number of online cancer prognostic tools becoming available. Considerable heterogeneity exists in how uncertainties are described in these tools. The community is not equipped to communicate results of precision medicine. Abstract: Objective To review how web-based prognosis tools for cancer patients and clinicians describe aleatory (risk estimates) and epistemic (imprecision in risk estimates) uncertainties. Methods We reviewed prognostic tools available online and extracted all uncertainty descriptions. We adapted an existing classification and classified each extracted statement by presentation of uncertainty. Results We reviewed 222 different prognostic risk tools, which produced 772 individual estimates. When describing aleatory uncertainty, almost all (90%) prognostic tools included a quantitative description, such as "chances of survival after surgery are 10%", though there was heterogeneity in the use of percentages, natural frequencies, and use of graphics. Only 14% of tools described epistemic uncertainty. Of those that did, most used a qualitative prefix such as "about" or "up to", while 22 tools described quantitative descriptions using confidence intervals or ranges. Conclusions Considerable heterogeneity exists in the way uncertainties are communicated in cancer prognostic tools. Few tools describe epistemic uncertainty. This variation is predominately explained by a lack of evidence and consensus in risk communication, particularly for epistemic uncertainty. Practice Implications As precision medicine seeks to improve prognostic estimates, the community may not be equipped with the tools to communicate the results accurately and effectively to clinicians and patients.